2009
DOI: 10.1111/j.1439-0396.2008.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean peptides on growth performance, intestinal structure and mucosal immunity of broilers

Abstract: Five-hundred 1-day-old broilers were randomly assigned to five groups, 100 chickens for each group. From group 1 to 3, 80, 120 and 200 mg/kg soybean peptides was added to the diets respectively; in the fourth group, 3.2 mg/kg genramycin was added; and the fifth group was the control without soybean peptides and antibiotics. At the age of 28 and 49 days, the number of goblet cells (GC), intestine intraepithelial lymphocyte, immunoglobulin A-forming cells, the ratio of villous height and crypt depth (V/C) of bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Hematoxylin and eosin stain was applied for the histological observation from S1 to S9, following the methods described by Jiang et al (2009). The intestinal morphology was observed under an optical microscope (Olympus BX51, Japan).…”
Section: Paraffin Sectioning Of Turtle Intestine Hematoxylin and Eosmentioning
confidence: 99%
“…Hematoxylin and eosin stain was applied for the histological observation from S1 to S9, following the methods described by Jiang et al (2009). The intestinal morphology was observed under an optical microscope (Olympus BX51, Japan).…”
Section: Paraffin Sectioning Of Turtle Intestine Hematoxylin and Eosmentioning
confidence: 99%
“…Under ITF stimulation, the Vangl1 protein may be Ser/Thr phosphorylated, the cross-linking of cell membrane and E-cadherin may disappear, and cell migration may be accelerated once mucosal repair begins [22].To verify the effect of hITF gene therapy, after preparing mice model with severe burns, we gavaged them with recombinant adenovirus and then detected the specimens at specific points in time. The CMDI judges injury severity [23]. Our study results showed that intestinal mucosa injury appeared early in pathogenesis and demonstrated heavy damage and obvious pathological changes one day after the burn, while the post-injury CMDI was significantly higher than the pre-injury CMDI, became worse, and peaked 3 days after the burn.…”
Section: Discussionmentioning
confidence: 67%
“…A diet with 200g/kg soy peptide inclusion level fed to Juvenile Japanese flounder could improve growth performance (Mamauag et al, 2011). There is a positive effect on weight gain of broilers (Jiang, Yin, & Yang, 2009) and weanling pigs (Min et al, 2004) when soybean peptides were supplemented in feed. The present study demonstrated that fishmeal substituted with CPH can improve the WG.…”
Section: Discussionmentioning
confidence: 99%